Relationship between social-emotional competence and teaching skills of secondary school teachers - Zarim, Nor Zairos Abu; Surat, Shahlan (Journal of Education and Learning (EduLearn), 2026)
This study explores the relationship between social-emotional competence (SEC) and teachers’ teaching skills (TTS) among a sample of 328 secondary school teachers in the Petaling Utama District, Selangor. The quantitative research employs the social, and emotional learning (CASEL) model to assess SEC and the Malaysian Teacher Standards provided by the Ministry of Education to evaluate TTS. The findings indicate that the overall level of TTS is slightly higher, with an average score of 3.282, compared to the SEC’s average score of 3.212. through Pearson correlation analysis, the study identifies a significant positive relationship between various SEC elements such as self-awareness (SA), self-management (SM), social awareness (SOA), relationship skills (RS), and making rational decision (MRD) and TTS, with RS demonstrating the highest correlation at r=0.562, p0.05. Further analysis using multiple regression reveals that SEC elements significantly contribute to variations in TTS, with SM emerging as the most significant predictor, showing a Beta value of 0.248 (24.8%). The study underscores the critical role that SEC plays in enhancing TTS, suggesting that beyond traditional training, a more in-depth and sustained focus on developing SEC could lead to significant improvements in teacher competency. Future research is recommended to continue exploring this connection to further enhance educational outcomes.